EFEKTIFITAS TERAPI DZIKIR TERHADAP TINGKAT KECEMASAN PADA PASIEN PRE OPERATIF OPEN REDUKSI FIKSASI INTERNAL - Irna " Yanti; Siti Rahmalia Hairani Damanik; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract A fracture is the disconnection of the integrity of the bone and cartilage, which covers damage on sum-sum of the bone, periosteum and surrounding soft tissues. This research aims to know the effectiveness of Dzikir therapy anxiety level in patients pre-operative open reduction internal fixation in the goverment hospitaL Arifin Achmad Pekanbaru. This research used Quasi Experimental design approach with One Grouppretest-posttest. The intervention was taken  10 minutes before 6 hours of surgery in the surgical ward. The total number of sample is 34 respondents was taken inclusion criteria by purposive sampling techniques. The data was colected by using instrument the Hamilton Anxiety Rating Scale (HOUSEHOLD). The data were analyzed by t-test dependent and the results showed there is significantly Dzikir therapy to reduce the level of anxiety among patients pre-op ORIF with  p value 0.000 < alpha (0.05). Based on the result of research that surgical nurse is need to provide guidance to the moeslem respondent to do Dzikir therapy before surgery intervention. Keywords: anxiety, dzikir therapy,  fracture